Ibadah-ibadah yang paling mudah / Abdul Malik Muhammad Al-Qasim ; penerjemah, Abdul Mustaqim, Muhammad Nur Wakhid ; penyunting, A. Choiran Marzuki - Al-Qasim, Abdul Malik Muhammad; Abdul Mustaqim; Wakhid, Muhammad Nur; Marzuki, A. Khoiran (Mitra Pustaka, 1999)
119 hlm. ; 20 cm. (2 eks)